P-118 Supported: the development of an abdominal support garment for people with ascites. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Preston, Nancy; Rigby, Janet; Griggs, Anita; Salt, Susan; Holmes, Rachael; Wright, Debbie
Abstract : Background: Ascites, a palliative symptom, is the build-up of large volumes of fluid in the peritoneal cavity which is drained at around five litres. If an indwelling catheter isn't possible then living with large volumes of fluid which are intermittently drained, is very uncomfortable. Earlier research showed that an abdominal support garment improved discomfort and provided support to their large distended abdomens (Preston 2004). However, the garment was too warm and also 'rode up' making it difficult to wear especially in warmer weather. Aim: To assess the acceptability of a support garment for use with people with ascites. Methods: Five prototypes for a support garment using a range of materials to offer abdominal support were developed with the company Jobskin. The ongoing study with eight participants with ascites (alcohol related liver disease and malignancy) will assess wear-ability and support requirements including an assessment of comfort, ease of putting on/off, mobility and acceptability. The garment, shaped like cycling shorts, can be made in a range of sizes and colours. Results: A garment was developed using five sections offering different types of pressurised support including a main abdominal area which allows for support but can significantly increase to allow for abdominal growth. The support garment supported an increase in abdominal girth from 70 cm to 110 cm in the initial participant yet remained comfortable. Early results have had it described as 'invaluable' by one doctor at the end of life of a patient to help her get in and out of bed when drainage was no longer an option. Interpretation and conclusions: A support garment has been created which can allow for increased abdominal girth yet provide abdominal support. Early indications show it is very acceptable, improves discomfort and offers the support required.